Population dynamics of cuscus in tourist island of Ahe, District of Nabire, Papua - ANTON SILAS SINERY; CHANDRADEWANA BOER; WARTIKA ROSA FARIDA (Biodiversitas Journal of Biological Diversity, 2013)
Sinery AS, Boer C, Farida WR.2013. Population dynamics of cuscus in tourist island of Ahe, District of Nabire, Papua. Biodiversitas 14: 95-100. Cuscus is a pouched herbivorous mammal of the family Phalangeridae which is arboreal and nocturnal.. The animals are protected by law because, in addition to having a low reproduction and limited distribution area, they face a very high level of hunting. Hunting in the wild by people is done not only in production forest areas but also in forest conservation areas such as recreational forest of Table Mountain, Arfak Mountains Nature Reserve, and other places. Directly or indirectly, the hunting affects the quality of the ecosystem in these areas, especially the cuscus population. Better management efforts are required in these areas to ensure the survival of many organisms in it, especially the cuscus. This study aimed to determine the cuscus population in Ahe Island, and the method applied was descriptive method using direct observation. The study was conducted in one month. The results demonstrate that cuscus in Ahe Island consisted of common spotted cuscus (Spilocuscus maculatus) and eastern cuscus (Phalanger orientalis). The number of individuals of S. maculatus was 24, consisting of 14 females and 10 males, whereas P. orientalis consisted of 2 individuals and both were males. The number of adult cuscus individuals was 16, while adolescents and children, were respectively 8 and 2. At least 10 plant species were identified as a source of feed for cuscus in Ahe Island recreation area. Plant parts consumed by cuscus were fruit and young leaves, but based on level of need, most of the cuscus consumed fresh fruit because of its sweet taste and high water content that helps the digestive process.